The mutation of Trp64Arg in β3-adrenoreceptor-encoding gene is significantly associated with increased hypertension risk and elevated blood pressure: a meta-analysis - Yang, Hualing (Oncotarget, 2017)
This meta-analysis was implemented to test the association of a missense mutation, Trp64Arg, in β3-adrenoreceptor-encoding gene (ADRB3) with both hypertension risk and blood pressure (BP) changes. A systematic search of three publicly-available databases was launched to look for articles published as of December 2016. Qualification appraisal and data extraction were independently done by two researchers. Pooled estimates were expressed as odds ratio (OR) or weighted mean difference (WMD), and their 95% confidence intervals (95% CIs). There were separately 21 (3750/4225 patients/controls) and 17 (6100 subjects) individual studies for hypertension risk and BP changes. Integral analyses revealed that Trp64Arg mutation was associated with the significantly increased risk of hypertension, and particularly, the 64Trp/64Arg heterozygote carriers were 1.23-times more likely to develop hypertension compared with the 64Trp/64Trp homozygote carriers (OR = 1.23, 95% CI: 1.02∼1.46, P = 0.021). Publication bias was extremely low for all integral comparisons. In stratified analyses, significance was spotted in populations of Chinese descent, in retrospective studies, in hospital-based studies, in age-matched case-control studies, in studies enrolling patients with mean body mass index < 25 kg/m(2) and in studies with total sample size ≥ 240. Heterogeneity was improved for most stratified comparisons. Further in hypertensive patients, the 64Trp/64Arg heterozygote carriers had significantly higher systolic (WMD = 0.87 mmHg, 95% CI: 0.39∼1.35, P < 0.001) and diastolic (WMD = 0.88 mmHg, 95% CI: 0.59∼1.17, P < 0.001) BP than 64Trp/64Trp homozygote carriers. Altogether, ADRB3 gene Trp64Arg mutation was significantly associated with an increased predisposition toward hypertension and elevated systolic/diastolic BP in hypertensive patients, suggesting that Trp64Arg is an important hypertension-susceptibility marker.